Current screening approaches for antibody deficiency. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: Diagnostic delay is a major problem for rare diseases including primary antibody deficiency (PAD). The aim of this review is to discuss the opportunities and challenges of current and future screening approaches for antibody deficiency, to reduce the delay and its impact on patients. Recent findings: Diagnostic delay in PAD is known to result in increased morbidity, mortality, and permanent functional impairment. Approaches to prevent this have been only partially successful and the delay may still be many years as the clinical presentation of PAD is highly variable and may be at any age, making screening difficult. Patients often have numerous healthcare encounters generating repeated cycles of laboratory and clinical data before the diagnosis is made. Low immunoglobulin levels result in alterations in laboratory tests not directly aimed at measuring immunoglobulins. We describe these and highlight the growing evidence in support of using calculated globulin which is part of the liver function test profile as a screening tool for antibody deficiency. Additional approaches include using embedded algorithms to analyse data generated by repeated clinical encounters (e.g. infections, antibiotics, cytopenias), potentially in combination with laboratory results such as calculated globulin, to help bring forward the diagnosis of PAD in patients in whom this has not yet been considered. Summary: There is a strong case for the use of calculated globulin in screening for antibody deficiency. Further work is required to integrate laboratory results with clinical data to reduce diagnostic delay in patients with hitherto unsuspected antibody deficiency.